Integrating Islamic Communication and Spiritual Coping Mechanisms: A Review of Stress Management Strategies in the Malaysian Context - Maszlee Mahmud; Basyouni Basyouni (PT. Berkah Smart Academica, 2025)
The escalation of mental health disorders in Malaysia following the global pandemic necessitates intervention strategies that are more socioculturally relevant than conventional secular models, which frequently overlook the dimension of spirituality. This study aims to evaluate and formulate the integration of Islamic communication principles and spiritual coping mechanisms as a holistic stress management strategy within the Malaysian context. The methodology employed is a Systematic Literature Review (SLR) utilizing the PRISMA protocol and content analysis techniques on 45 reputable journal references published between 2021 and 2025. Data indicates that prophetic communication principles, such as Qaulan Layyina and Qaulan Sadida, combined with positive spiritual coping—specifically tawakkul and sabar—significantly enhance psychological resilience and reduce cortisol levels in distressed individuals. The research findings conclude that integrating transcendental values into stress management protocols is not merely an alternative but a fundamental necessity for achieving sustainable inner tranquility (thumaninah). This study recommends a reform of Malaysia’s national mental health policies through cross-disciplinary collaboration between clinical psychologists and psychospiritual experts to create intervention models that are inclusive and grounded in local cultural identity.